1999
DOI: 10.3322/canjclin.49.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Global cancer statistics

Abstract: Rates for five broad age groups (0-14, 15-44, 45-54, 55-64, and 65 and over) and sex were estimated for as many individual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
4,393
9
184

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,635 publications
(4,642 citation statements)
references
References 15 publications
31
4,393
9
184
Order By: Relevance
“…Although the incidence rates vary greatly within the same country or region and the incidence rates of PC are generally higher in Western countries than in China [1], many recent reports have indicated that the incidence of PC in China is increasing rapidly. For example, in Shanghai, it is estimated that the incidence of PC increased from 1.8 to 2.4 per 100 000 in 1990 to 4.5-7.7 per 100 000 in 2 000 and to about 10.0 per 100 000 in 2004 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence rates vary greatly within the same country or region and the incidence rates of PC are generally higher in Western countries than in China [1], many recent reports have indicated that the incidence of PC in China is increasing rapidly. For example, in Shanghai, it is estimated that the incidence of PC increased from 1.8 to 2.4 per 100 000 in 1990 to 4.5-7.7 per 100 000 in 2 000 and to about 10.0 per 100 000 in 2004 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis finds that excess body weight is associated with an increased risk of liver cancer. Although relatively rare in the United States and other developed countries, liver cancer is the third most common cause of death from cancer worldwide (Parkin et al, 2005). It is rarely detected early and is often fatal within a few months of diagnosis.…”
mentioning
confidence: 99%
“…1 In South Korea, gastric cancer has a higher incidence than any other cancer, and is the third most common cause of death from cancer. 2 The prognosis of patients with gastric cancer is influenced by the presence of lymph node (LN) metastasis, therefore, an accurate and reliable indicator is required to predict the presence of LN metastasis.…”
mentioning
confidence: 99%